2018
DOI: 10.1002/lary.27472
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term analysis of transorally resected p16 + Oropharynx cancer: Outcomes and prognostic factors

Abstract: High 5-year survival and locoregional control were observed, with recurrence occurring more commonly as distant metastasis. The observed time to recurrence suggests posttreatment oncologic surveillance for at least 48 months. Identified prognosticators will inform adjuvant treatment considerations, trial planning, and patient counseling for long-term outcomes. Laryngoscope, 2018 LEVEL OF EVIDENCE: 2b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 54 publications
(134 reference statements)
13
36
0
Order By: Relevance
“…However, there are few studies that examine smoking status in the context of AJCC‐8 staging guidelines. Similar to other work, our results showed a negative association between higher AJCC‐8 stage and survival as well as smoking and survival in HPV‐positive disease . Unlike previous research, our study estimates the prognostic significance of smoking while adjusting for AJCC‐8 stage and looks at the combined effects of stage and smoking status.…”
Section: Discussionsupporting
confidence: 84%
“…However, there are few studies that examine smoking status in the context of AJCC‐8 staging guidelines. Similar to other work, our results showed a negative association between higher AJCC‐8 stage and survival as well as smoking and survival in HPV‐positive disease . Unlike previous research, our study estimates the prognostic significance of smoking while adjusting for AJCC‐8 stage and looks at the combined effects of stage and smoking status.…”
Section: Discussionsupporting
confidence: 84%
“…This investigation represents the largest series of elderly patients treated with TOS for HPV‐related OPSCC. We found that patients 70 years or older have similar 3‐year disease‐specific oncologic outcomes (DSS, 94.3%; DFS, 79.3%) compared to published series analyzing younger cohorts . As expected, OS (81.5%) was lower than the 83%‐90% typically reported for HPV‐associated OPSCC, secondary to 21.3% dying of unrelated causes .…”
Section: Discussionsupporting
confidence: 75%
“…We found that patients 70 years or older have similar 3‐year disease‐specific oncologic outcomes (DSS, 94.3%; DFS, 79.3%) compared to published series analyzing younger cohorts . As expected, OS (81.5%) was lower than the 83%‐90% typically reported for HPV‐associated OPSCC, secondary to 21.3% dying of unrelated causes . Our analysis of these data demonstrated that elderly adults with HPV‐associated OPSCC could be subcategorized into three groups, allowing us to describe a clinically relevant decrement in 3‐year OS from 100% to 54% with rising age, ACE‐27 comorbidity score, and cT stage.…”
Section: Discussionsupporting
confidence: 70%
“…The few studies to date that have characterized recurrence-associated factors specifically in HPV-OPC have identified primary tumor category, lymph node category, and tobacco use. 4,23,[29][30][31] High-risk disease features known to be prognostic for RFS in HPV-negative HNSCC but of unclear prognostic significance in HPV-OPC include primary tumor resection margin status, LVI, PNI, and ENE. [32][33][34][35][36] Combinations of these clinicopathologic factors are currently in place to stratify risk in deintensification studies.…”
Section: Discussionmentioning
confidence: 99%